Skimmer CID‒ion trap mass spectrometry of phosphotyrosine‒containing peptides. Issue 3 (2004) - Zolodz Zolodz, Melissa D. Melissa D.; Wood Wood, Karl V. Karl V.
Abstract : Proteomic analysis is becoming a popular field in science. Analysis of protein modifications is useful in deciphering cellular functions and errors in pathways that can result in disease. There has been increased interest in the phosphotyrosine proteome. Due to the difficulty in finding the location of the tyrosine phosphorylation site in the tyrosine phosphorylated peptide or even to verify that the parent protein is a phosphotyrosyl‒protein, new analytical tools are being developed. The phosphotyrosine immonium ion can be produced via skimmer CID for detection via ion trap mass spectrometry and is a useful marker for the indication of the presence of a phosphotyrosine residue. Skimmer CID analysis can also be used to differentiate phosphotyrosine‒containing peptides from other phosphorylated peptides. In this study, phosphotyrosine‒containing peptides were analyzed by skimmer CID in an ion trap mass spectrometer. The factors affecting the signal abundance of the phosphotyrosine immonium ion were investigated.